Covid-19 Case with Mild Pneumonia - Mukhtar Ikhsan (Faculty of Medicine, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2021)
Background: On December 31, 2019, WHO China Country Office reported a case of pneumonia of unknown etiology in Wuhan City, China. On January 7, 2020, China identified pneumonia of unknown etiology as a grew type of coronavirus (coronavirus disease, COVID-19).Case report: A 39-year-old woman – health care worker - came to the hospital with the chief complaint of coughing three days earlier. Dry cough with no phlegm, fever and no shortness of breath. There are also no other complaints. On physical examination found no abnormalities. There is no history of traveling abroad but there is a history of contact with sufferers of COVID-19 when treating patients. Patients diagnosed as acute respiratory infection were given cefixim 2 x 200 mg for 5 days, paracetamol if necessary and vitamins. Chest X-ray examination is normal while CT X-ray examination without contrast shows a picture of ground glass opacity (GGO). The PCR swab was found to be positive. The patient was diagnosed as positive for COVID-9 with Mild Pneumonia. The patient underwent independent isolation by taking the hydrochloroquin sulfate on day 1: 2 x 2 tab, days 2 - 14: 2 x 1 tab. In addition, the patient also took 1 x 1000 mg of Vitamin C supplements, 1 x 200 IU of vitamin D3 and 1 x 20 mg of Zinc.Results:Clinical symptoms are getting better. On the chest CT scan, the GGO image has improved. The PCR swab turned negative. The patient with COVID-19 with Mild Pneumonia cured.